Studying the changes in the characteristics of radiation-protective composition materials in dependence on homogeneity of distributing of metal components - Prokhorenko, E.M.; Lytvynenko, V.V.; Zakharchenko, A.A.; Khazhmuradov, M.A.; Prokhorenko, T.G. (Вопросы атомной науки и техники, 2019)
The dependence of the hardness of polystyrene-metal composite materials on the homogeneity of the distribution of particles of a component over the volume of a composite material is investigated. Improvements are made to thermoplastic-automata, which make it possible to improve the quality of composites production. The methods of IR-radiometric diagnostics of the component mixing efficiency are improved. The speeds of the mixer blades are experimentally determined depending on the size and number of particles of the metal components. Radiation protective characteristics were obtained for composite materials by numerical methods. Analyzed the attenuation of the absorbed dose of ionizing radiation, depending on the energy of gamma-rays.